Analysis of Marketing Mix Strategy in Increasing Sales Volume at Samata House Coffee Shop Surabaya - Sabhina Agni Naenara; Budi Prabowo (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to evaluate the application of marketing mix strategies in increasing sales volume at Samata House Coffee Shop Surabaya. The method used is descriptive qualitative research with data collection techniques through observation, interviews, and documentation. The results showed that the 7P marketing mix strategy (product, price, place, promotion, people, process, and physical evidence) has a crucial role in increasing business attractiveness and competitiveness. SWOT analysis resulted in a factor score of 3.07 strengths, 0.26 weaknesses, 2.58 opportunities, and 0.56 threats. The IFAS and EFAS matrices scored 3.33 and 3.14, respectively, indicating the dominance of internal strengths and external opportunities. Based on the SWOT matrix analysis, Samata House is in Quadrant I, which recommends an aggressive growth strategy by leveraging internal advantages and external opportunities to increase sales volume. The Strength Opportunities (SO) strategy enhances competitiveness and market penetration amid the coffee shop industry’s competition.